1993
DOI: 10.1007/bf00454892
|View full text |Cite
|
Sign up to set email alerts
|

Early recovery of protein synthesis following ischemia in hippocampal neurons with induced tolerance in the gerbil

Abstract: Following brief cerebral ischemia, tolerance to subsequent ischemia is induced in the hippocampal neurons. In this experiment, recovery of protein synthesis was investigated autoradiographically in gerbils with induced tolerance. The animals were subjected to single forebrain ischemia for 5 min (5-min ischemia group) or 2 min (2-min ischemia group). To observe the effect of tolerance acquisition, double forebrain ischemia (double ischemia group), 2-min ischemia followed by 5-min ischemia was induced 2 days lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 35 publications
3
26
1
Order By: Relevance
“…In the normoxic group, 5-minute-forebrain ischaemia induced delayed neuronal death. These changes were similar to those reported in previous reports [13,14,22]. In the hypoxic group, the CAt pyramidal cells were more damaged after 5-minute-forebrain ischaemia than those in the normoxic group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the normoxic group, 5-minute-forebrain ischaemia induced delayed neuronal death. These changes were similar to those reported in previous reports [13,14,22]. In the hypoxic group, the CAt pyramidal cells were more damaged after 5-minute-forebrain ischaemia than those in the normoxic group.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that neurotoxic actions of synaptically released excitatory amino-acids play a crucial role in delayed neuronal damage [23,28], but the mechanism is not fully understood. Pre-treatment of the brain with a sublethal stress has been reported to increase neuronal tolerance to a subsequent episode of cerebral ischaemia [3,15,22]. In an in vitro study, hippocampal neurons have been reported to become more vulnerable to glutamate neurotoxicity after subcritical hypoxia [18].…”
Section: Introductionmentioning
confidence: 98%
“…However, Nakagomi et al (1993) showed that the recovery rate of protein synthesis in gerbil brain after ischemic preconditioning is more rapid than that in nonpreconditioned gerbils. These results indicate that ischemic preconditioning contributes to the early recovery of protein synthesis.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, preconditioning serves to genetically reprogram the response to ischemia [29]. Nonetheless, it is important to note that translation is deeply inhibited during early post-ischemic reperfusion [35], and is only partially restored by IT [31,51,52]. Therefore, translation might modulate the synthesis of the protein products of these inducible genes, and be responsible for the observed discrepancy between the messenger RNA (mRNA) and protein expression patterns [53].…”
Section: Discussionmentioning
confidence: 98%